Handgrip strength and hand dimensions in young handball and basketball players - Visnapuu, M.; Jürimäe, T. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Various sport settings require a sustained level of hand prehensile force to maximize control and performance (Blackwell et al. 1999). Handle shape and size can affect grip forces when different tasks are taken into consideration (Cochran and Riley, 1986). Aim The aim of this study was to investigate different hand dimensions and the effect of these on the handgrip strength in 10 to 13 year old male handball and basketball players. Methods In total, 133 players were studied. Players were divided into 4 groups: (1) 10 to 11 year old (n=34, 146.6± 6.9 cm, 37.7±6.1kg); (2) 12 to 13 year old (n=39, 160.1±9.2 cm, 47.1±8.0 kg) handball players; (3) 10 to 11 year old (n=38, 149.5±7.0 cm, 38.9±6.4 kg); (4) 12 to 13 year old (n=22, 160.2±9.3 cm, 48.6±11.3 kg) basketball players. All players were from teams participating in Estonian national championships. The following parameters of the dominant hand were measured: spread of fingers (5 dimensions - from tip of thumb to tip of index finger; from tip of thumb to tip of middle finger; from tip of thumb to tip of ring finger; from tip of thumb to tip of little finger and from tip of thumb to tip of each finger); length of fingers (5 dimensions - from joint of wrist to tip of each finger tip); circumferences (6 dimensions - from wrist joint to tip of thumb to tip of index finger and to wrist joint; from wrist joint to tip of thumb to tip of middle finger to wrist joint; from wrist joint to tip of index finger to tip of middle finger to wrist joint; from wrist joint to tip of middle, ring and little finger tip and to wrist joint; from tip of thumb to tip of index finger to tip of middle finger and back to tip of thumb; from wrist joint to tips of all fingers and to wrist joint;). Handgrip strength (hand dynamometer; Lafayette, USA) of dominant and non dominant hand was measured. Results Most of measured hand dimension values improved significantly with increasing age in handball players. Only some spreads of fingers (from tip of thumb to tip of index finger and to tip of thumb to tip of middle finger) did not improve. However, only length of fingers and some circumferences improved significantly with increasing age in basketball players. Hand dimensions in 12-13 year old handball players and basketball players did not differ significantly while most of spread of fingers and some circumferences (from wrist joint to tip of index to tip of middle finger to wrist joint, from wrist joint to tips of all fingers to wrist joint and from tip of thumb to tip of index finger to tip of middle finger and back to tip of thumb) were significantly longer in handball players. All hand dimensions in handball and basketball players in the age group 10-11 did not differ significantly. Handgrip strength with dominant and non dominant hand was significantly higher with increasing age in both handball and basketball players. There were significant relationships between handgrip strength with dominant hand and fingers length (r=0.57-0.73) and hand circumference values in basketball players at the age of 12-13 (r=0.56-0.77). Handgrip strength with dominant hand did not depend on the most values of spread of fingers. Only from tip of thumb to tip of little finger values related to handgrip strength in all studied groups (r=0.33-0.48). Conclusion It was concluded that the length of fingers and size of the hand but not spread of fingers depend on the handgrip strength in young handball and basketball players.